2008
DOI: 10.1111/j.1745-7262.2008.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the autonomic nervous system is an appropriate biological marker for the well-being in erectile dysfunction*

Abstract: Quantitative assessment of the ANS by heart rate variability analysis might be a suitable marker for well-being of patients with ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
2
10
0
2
Order By: Relevance
“…More broadly, findings may point toward the underlying role of HRV in the physiology of erectile hemodynamics. Results of the present investigation were in line with prior studies showing associations between healthy sympathovagal balance (i.e., relative enhancement in parasympathetic activity and diminution in sympathetic activity) and enhanced EF [24–27,43]. Moreover, these findings supplement the growing body of literature exploring relationships between HRV and sexual health more broadly.…”
Section: Discussionsupporting
confidence: 91%
“…More broadly, findings may point toward the underlying role of HRV in the physiology of erectile hemodynamics. Results of the present investigation were in line with prior studies showing associations between healthy sympathovagal balance (i.e., relative enhancement in parasympathetic activity and diminution in sympathetic activity) and enhanced EF [24–27,43]. Moreover, these findings supplement the growing body of literature exploring relationships between HRV and sexual health more broadly.…”
Section: Discussionsupporting
confidence: 91%
“…When sympatho-vagal balance expressed as LF/HF ratio was compared between the two groups under three different body positions (supine, seated, and standing position), LF/HF ratio of the disease subject was increased dramatically. Dogru et al [14] reported that ED group had significantly higher value of sympathetic activity indicator (LF/HF ratio) than the control group, but there was no difference between the two groups in terms of parasympathetic activity indicator (HF). These results support the idea that ED patients have excessive sympathetic activity and out study had similar results.…”
Section: Discussionmentioning
confidence: 99%
“…The digitized electrocardiography signals were analyzed by online database and stored on a hard disk for offline verification simultaneously. Two main analyses are performed for HRV: time domain and frequency domain analysis [14]. To compare the time domain indexes, we used mean heart rate (HR) in bpm, the standard deviation of all normal RR intervals (SDNN), and the square root of the mean differences between successive RR intervals (RMSSD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency power ([LF] 0.04–0.15 Hz) has less clear associations with health [1,3] and sexual function [10,42,43]. Hence, we examine, but do not hypothesize on any association of LF with sexual behaviors or lifetime number of PVI partners.…”
mentioning
confidence: 99%